Resveratrol and Alzheimer’s disease: message in a bottle on red wine and cognition - Granzotto, Alberto; Zatta, Paolo (Frontiers in Aging Neuroscience, 2014)
Cognitive impairment is the final outcome of a complex network of molecular mechanisms ultimately leading to dementia. Despite major efforts aimed at unraveling the molecular determinants of dementia of Alzheimer type (DAT), effective disease-modifying approaches are still missing. An interesting and still largely unexplored avenue is offered by nutraceutical intervention. For instance, robust epidemiological data have suggested that moderate intake of red wine may protect against several age-related pathological conditions (i.e.: cardiovascular diseases, diabetes, and cancer) as well as DAT-related cognitive decline. Wine is highly enriched in many polyphenols, including resveratrol. Resveratrol is a well recognized antioxidant which may modulate metal ion deregulation outcomes as well as main features of the Alzheimer’s disease (AD) brain. The review will discuss the potentiality of resveratrol as a neuroprotectant in dementia in relation to the oxidative stress produced by amyloid and metal dysmetabolism.